From smart grids to smart cities : new challenges in optimizing energy grids - La Scala, Massimo (Advanced SmartGrids set., 2017)
This title is aimed at showing methodologies and technological solutions for energy system monitoring and control, starting from applications to electricity smart grids and ending with more unconventional approaches to multi-carrier systems: microgrids and energy hubs.